Click'n'Roll: No Evidence of Illusion of Control - Antonio Filippin; Paolo Crosetto (Institute for the Study of Labor (IZA), 2015)
Evidence of Illusion of Control the fact that people believe to have control over pure chance events is a recurrent finding in experimental psychology. Results in economics find instead little to no support. In this paper we test whether this dissonant result across disciplines is due to the fact that economists have implemented only one form of illusory control. We identify and separately tests in an incentive-compatible design two types of control: a) over the resolution of uncertainty, as usually done in the economics literature, and b) over the choice of the lottery, as sometimes done in the psychology literature but without monetary payoffs. Results show no evidence of illusion of control, neither on choices nor on beliefs about the likelihood of winning, thus supporting the hypotheses that incentives crowd out illusion of control.
Keywords: B49; C91; D81; 330; Illusion of Control; experiment; risk elicitation; hypothetical bias